Bush at war: decision-making in Washington - Hossain, Ishtiaq (IIUM Press, 2003)
Bob Woodward, Assistant Managing Editor of the influential The Washington Post, has come up with his second book on an American presidency led by a member of the Bush family, Bush at War. 1 Bob Woodward’s first book on a Bush presidency is The Commanders. 2 This is an account of U.S. military decision-making during the first 800 days of the presidency of George Bush from November 8, 1988, when he was elected President, through January 16, 1991, the beginning of the first Gulf War. Convinced that the end of the Cold War would usher in a quiet period for the U.S. military, Woodward initially wanted The Commanders to focus on the intricacies of the U.S. military in peace time. But the Panama invasion of December 1989 and the 1990 Gulf Crisis changed all that. Deviating from his original intention, Bob Woodward ended up writing about the U.S. military decision-making during those military operations. However, The Commanders is not all about military decision-making either. Woodward’s analysis showed that the Pentagon was not always the centre of military decision-making process; during the first Gulf Crisis, the White House ran the show.